Multiple factors maintain assembled trans-SNARE complexes in the presence of NSF and αSNAP - Prinslow, Eric A; Stepien, Karolina P; Pan, Yun-Zu; Xu, Junjie; Rizo, Josep (eLife, 2019)
Neurotransmitter release requires formation of trans-SNARE complexes between the synaptic vesicle and plasma membranes, which likely underlies synaptic vesicle priming to a release-ready state. It is unknown whether Munc18-1, Munc13-1, complexin-1 and synaptotagmin-1 are important for priming because they mediate trans-SNARE complex assembly and/or because they prevent trans-SNARE complex disassembly by NSF-αSNAP, which can lead to de-priming. Here we show that trans-SNARE complex formation in the presence of NSF-αSNAP requires both Munc18-1 and Munc13-1, as proposed previously, and is facilitated by synaptotagmin-1. Our data also show that Munc18-1, Munc13-1, complexin-1 and likely synaptotagmin-1 contribute to maintaining assembled trans-SNARE complexes in the presence of NSF-αSNAP. We propose a model whereby Munc18-1 and Munc13-1 are critical not only for mediating vesicle priming but also for precluding de-priming by preventing trans-SNARE complex disassembly; in this model, complexin-1 also impairs de-priming, while synaptotagmin-1 may assist in priming and hinder de-priming.
Keywords: neurotransmittersrelease; N-ethylmaleimide sensitive factor; alphaSNAP; SNAREs; Munc18-1; Munc13